The legal nature of the principle of openness in criminal proceedings - N., Mukhamadyeva G.; O., Bayandina M.; T., Nurmaganbet E.; A, Kudratov M. (Farabi Journal of Social Sciences, 2019)
The article examines the legal nature of the principle of transparency as a fundamental guideline and start the criminal process of the Republic of Kazakhstan. Actualized the need for further improvement of the legislation defining the basic elements of a mechanism for implementing public. The questions of the need to identify ways to increase openness in criminal proceedings.